2011
DOI: 10.1007/s00296-010-1726-5
|View full text |Cite
|
Sign up to set email alerts
|

Beta2-glycoprotein I gene polymorphisms Val247Leu and Trp316Ser in Spanish patients with primary antiphospholipid syndrome

Abstract: The significance of beta2-glycoprotein I (β2GPI) polymorphisms in the production of anti-β2GPI and other antiphospholipid autoantibodies (aPL) and in the pathogenesis of primary antiphospholipid syndrome (PAPS) is not well understood. We performed a study comparing the distribution of polymorphisms at codons 247 (Val247Leu) and 316 (Trp316Ser) of the β2GPI gene in a Caucasian Spanish population of PAPS patients and healthy controls, and then making correlations with the development of anti-β2GPI antibodies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…Ysuda et al [5] also showed an increased frequency of V/V genotype among Japanese patients. In contrast, Pardos-Gea et al [15] reported that the genotype and allele frequencies of the b 2 GPI gene were not correlated with thrombosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ysuda et al [5] also showed an increased frequency of V/V genotype among Japanese patients. In contrast, Pardos-Gea et al [15] reported that the genotype and allele frequencies of the b 2 GPI gene were not correlated with thrombosis.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, Pardos‐Gea et al . reported that the genotype and allele frequencies of the β 2 GPI gene were not correlated with thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…In unselected Chilean patients, it was associated with venous and arterial thrombosis but not aβ 2 GPI [ 41 ] . In contrast, 3 studies did not fi nd a relationship between the Val/Leu 247 polymorphism and aβ 2 GPI and/or primary APS in Caucasian patients [ 40 ] , Polish Caucasian patients [ 46 ] , or Spanish Caucasian patients [ 47 ] . Comparisons of cross-sectional autoantibody measures with genetic variants may be diffi cult to interpret since there remains poor standardization of these assays and critical autoantibodies may not be detectable on a single sample taken once in the lifetime of a patient.…”
Section: Human Leukocyte Antigen (Hla) Associationsmentioning
confidence: 81%
“…This genotype frequency is elevated in APS patients, especially in those with thrombosis (50). These studies pointed out to selectin-PSGL1 system genetic variations as determinant of thrombotic predisposition in patients with APS.Two single nucleotide variations in β2-Glycoprotein gene have been found increased in APS: G796T and G1004C, more known by the changes in aminoacidic sequence; Val247Leu and Trp316Ser, respectively (58, 59). The presence of these SNVs may lead to a conformational change in β2GPI that affects the exposure of potential epitopes, which in turn may favor thrombosis.…”
Section: Genetic Risk Factors Of Athero-thrombosis In Apsmentioning
confidence: 99%
“…However, the relationship with either arterial or venous thrombosis is not clear (59). In the same way, the presence of Trp316Ser SNV may increase the risk of APS, but there is no relationship with thrombosis or antibodies production (58). Thus, further studies might be required to evaluate the pathogenic link between these SNVs and thrombosis in APS.Pierangeli et al evaluated the prevalence of two SNVs in Toll-like receptor 4 (TLR4) gene in 100 APS patients: A896G and C1196T.…”
Section: Genetic Risk Factors Of Athero-thrombosis In Apsmentioning
confidence: 99%